KOMPLEKSITAS STRUKTUR NARATIF DALAM NOVEL LA DENTELLIÈRE KARYA PASCAL LAINÉ - Tania Intan (Universitas Hasanuddin, 2020)
This study aims to explore the complexity of the narrative structure of the novel La Dentellière (The Lacemaker) by Pascal Lainé, the French who wins Prix Goncourt in 1974. The book talks about different understandings of the love of two characters, Pomme and Aimery, which are narrated with complex storytelling techniques. The discussion in this paper focuses on the storytelling strategy with the analysis of perspective and diegesis perspective angling techniques. The research method used is descriptive analysis with objective approach. Data in the form of words, phrases, and sentences were collected from la Dentellière's novel with literature study techniques. The results of this study indicate that the theme of love which is considered simple can be multi-interpretative when told with a variety of points of view. The problem of social and educational disparity between the two figures has an impact on differences in understanding of the concept of love that is not bridged by tolerance, understanding, and good communication.